Improvement of the stability of TiSnSb anode under lithiation using SEI forming additives and room temperature ionic liquid/DMC mixed electrolyte. (10th July 2015) - Zhang, W.; Ghamouss, F.; Mery, A.; Lemordant, D.; Dedryvère, R.; Monconduit, L.; Martinez, H.
Highlights: Lithiation and delithiation of TiSnSb conversion anode material Room temperature ionic liquid based electrolyte Fluoroethylene carbonate SEI builder additives XPS and electrochemical analysis of the anode/electrolyte interface Abstract: The electrochemical behavior and the stability under cycling of TiSnSb anode for Li-ion batteries were investigated in room temperature ionic liquids based electrolyte. X-ray photoelectron spectroscopy (XPS), cyclic voltammetry, and electrochemical impedance (EIS) measurements have been performed to study the formation of surface film on the TiSnSb anode. Surface analysis was performed by a combined XPS core peaks and quantification data analysis, to establish the main components of the solid electrolyte interphase film (SEI). The key observation is that the thickness and the chemical nature of the SEI layer is strongly related to the electrolyte formulation and the addition of SEI layer forming additives. Vinylene carbonate (VC) and fluoroethylene carbonate (FEC) were applied in order to improve the anode/electrolyte interface. From XPS, EIS results and galvanostatic cycling the role of additives and ionic liquids as an effective stability improver has been highlighted.